P39 Establishing minimally important differences for cardiac MRI endpoints in pulmonary arterial hypertension. (11th November 2022) - Alabed, S; Garg, P; Alandejani, F; Dwivedi, K; Maiter, A; Karunasaagarar, K; Rajaram, S; Hill, C; Thomas, S; Sharkey, M; Wild, JM; Watson, L; et al.
Abstract : Introduction: Cardiac MRI (CMR) is the gold standard technique to assess bi-ventricular volumes and function and is increasingly being considered as an end-point in clinical studies. Currently, with the exception of right ventricle (RV) stroke volume, there are no minimally important differences (MIDs) reported for CMR metrics. Our study aimed to identify MIDs for CMR metrics based on FDA recommendations for a surrogate end-point that should reflect how a patient feels, functions and survives. Methods: Consecutive treatment-naive patients with PAH between 2010 and 2021 who had two CMR scans (at baseline and at 12 months following treatment) were identified from the ASPIRE registry. All patients were followed up for one additional year after the second scan. The MID in CMR metrics was determined using two methods; (i) an anchor-based method combining how a patient 'feels' (emPHasis-10 questionnaire) and 'functions' (incremental shuttle walking test) and (ii) for 'survives' a distribution-based method for one-year mortality. RV ejection fraction (RVEF) and RV and left ventricle (LV) end-diastolic volume, RV end-systolic volume and LV stroke volume were measured at baseline and follow-up. For each metric, relative difference (ratio of absolute difference to baseline measurement) was compared in a Cox-regression and Kaplan-Meier-analysis. Results: 239 patients were included. The MIDs ( P <0.05), for metrics for how a patient 'feels and functions' for i) improvement, were a relative increase in RVEF, LVSV or LVEDV of 5% and a decrease in RVESV or RVEDV of 7% and 5%, respectively and for ii) clinical worsening, were a relative reduction in RVEF of 10%, reduction of LVSV or LVEDV of 5% or an increase in RVESV of 14%. For 'survives' the MID associated with (i) a reduced one-year mortality was an 8% relative reduction in RVESV and a 12% relative increase in LVEDV and (ii) increased one-year mortality were a 10% relative decrease in RVEF, an 22% increase in RVESV, a 6% increase in RVEDV, a 20% reduction in LVEDV and a 12% reduction in LVEDV. Conclusion: This study establishes clinically relevant CMR MIDs for how a patient feels, functions and survives in response to PAH treatment. These findings provide further support for the use of CMR as a clinically relevant surrogate end-point and will aid trial-size calculations for studies using CMR.